1990
DOI: 10.4153/cjm-1990-017-6
|View full text |Cite
|
Sign up to set email alerts
|

The Pexider Functional Equations in Distributions

Abstract: The Cauchy functional equations have been studied recently for Schwartz distributions by Koh in [3]. When the solutions are locally integrate functions, the equations reduce to the classical Cauchy equations (see [1]):(1) f(x+y)=f﹛x)+f(y)(2) f(x+y)=f(x)f(y)(3) f(xy)=f(x)+f(y)(4) f(xy)=f(x)f(y).Earlier efforts to study functional equations in distributions were given by Fenyö [2]for the Hosszu’ equationsf(x + y - xy) +f(xy) =f(x) +f (y ),by Neagu [4]for the Pompeiu equationf(x+y+xy)=f(x)+f(y)+f(x)f(y)and by Swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…In order to represent the left-hand side of equation (1.2), one needs to define two additional operators.This will be discussed in the next section. Moreover, we remark that the operator (2+ is similar to the operator Q defined and studied in [8,12]. The adjoints of these operators are Q* and Q*_ and are defined from 2'{I) into 2'il2) by…”
Section: ) Dxp[s; T] = P[ds; T] and D2p[s; T] = P[s; Dt]mentioning
confidence: 95%
See 2 more Smart Citations
“…In order to represent the left-hand side of equation (1.2), one needs to define two additional operators.This will be discussed in the next section. Moreover, we remark that the operator (2+ is similar to the operator Q defined and studied in [8,12]. The adjoints of these operators are Q* and Q*_ and are defined from 2'{I) into 2'il2) by…”
Section: ) Dxp[s; T] = P[ds; T] and D2p[s; T] = P[s; Dt]mentioning
confidence: 95%
“…The proof of this proposition can be carried out exactly as in [8]. The product operator F will be used, therefore, to represent the product f{x)g{y) of equation (1.2) when the equation is interpreted in distributions.…”
Section: ) Dxp[s; T] = P[ds; T] and D2p[s; T] = P[s; Dt]mentioning
confidence: 99%
See 1 more Smart Citation
“…Many well-known functional equations have been studied in the Schwartz distributions (see [2], [3], [4], [5], [10] and [11] etc.). Actually it was shown that most of these functional equations in the distributions reduce to the classical ones.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, in this paper we reformulate the following classical functional equations in Gevrey distributions: (1) f (x + y) = f(x) + f(y), (2) f (x + y) = f(x) · f(y),…”
Section: Introductionmentioning
confidence: 99%